Buffer and switch : road-to-road routing scheme for intermittently connected vehicular networks - Song, Chao (2013)
Due to the road-constrained data delivery and highly dynamic topology of vehicle nodes in a Vehicular Ad Hoc Network (VANET), it is better to construct routing based on the road-to-road pattern than the traditional node-to-node routing pattern in MANETs. However, the challenging issue is the opportunistic forwarding at intersections. Therefore, we propose a novel routing scheme, called Buffer and Switch (BAS). In BAS, each road buffers the data packets with multiple duplicates propagation in order to provide more opportunities for packet switching at intersections. Different from conventional protocols in VANETs, the propagation of duplicates in BAS is bidirectional along the routing path. Moreover, BAS's cost is much lower than other flooding-based protocols due to its spatio-temporally controlled duplicates propagation. Different from recent researches, BAS can deliver packets not only to a stationary node, but also to the stationary or mobile nodes in a specified area. We conduct the extensive simulations to evaluate the performance of BAS based on the road map of a real city collected from Google Earth. The simulation results show that BAS can outperform the existing protocols, especially when the network resources are limited.